Effects of boron application on new wheat varieties in Bangladesh (Bangladesh Journal of Agricultural Research, 2019)
A pot experiment was conducted in the Net house of Soil Science Division of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during rabi season, 2017-2018 in Tista Meander Floodplain Soils (AEZ-3). The objectives were to evaluate the effect of boron on the yield of wheat, estimate boron use efficiency and to find out suitable variety for maximizing the yield. The experiment was designed in Completely Randomized Design (CRD) with three replications. Three varieties of wheat (BARI Gom-28, BARI Gom-29 and BARI Gom-30) with 5 levels of boron (0, 0.5, 1.0, 1.5 and 2 kg ha-1) along with a blanket dose N120P30K90S15Zn3Mg6 kg ha-1 were used in the study. All the three varieties performed well with application of 1.5 kg B ha-1 as compared to the other B treatments. However, the highest yield (39.2 g pot-1) was obtained with BARI Gom-30 variety receiving B at 1.5 kg ha-1.Bangladesh J. Agril. Res. 44(2): 303-310, June 2019